Free Time : The Forgotten American Dream - Hunnicutt, Benjamin (Book collections on Project MUSE., 2013)
Has the "American Dream" become an unrealistic utopian fantasy, or have we simply forgotten what we are working for? The author examines the way that progress, once defined as more of the good things in life as well as more free time to enjoy them, has come to be understood only as economic growth and more work, forevermore. The author provides an incisive intellectual, cultural, and political history of the original "American Dream" from the colonial days to the present. Taking his cue from Walt Whitman's "higher progress," he follows the traces of that dream, cataloging the myriad voices that prepared for and lived in an opening "realm of freedom." This book reminds Americans of the forgotten, best part of the "American Dream" - that more and more of our lives might be lived freely, with an enriching family life, with more time to enjoy nature, friendship, and the adventures of the mind and of the spirit.